2010
DOI: 10.1055/s-0030-1262900
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Management of Sleep Disturbance during the Menopause Transition

Abstract: Sleep disturbances in midlife women are common and have been associated with the menopause transition itself, symptoms of hot flashes, anxiety and depressive disorders, aging, primary sleep disorders (i.e., obstructive sleep apnea, periodic limb movement disorder), comorbid medical conditions and medications, as well as with psychosocial and behavioral factors. Because there are several common sources of sleep problems in midlife women, the cause of an individual woman's sleep disturbance may be multifactorial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
127
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 163 publications
(137 citation statements)
references
References 145 publications
(235 reference statements)
7
127
0
3
Order By: Relevance
“…Studies of midlife women with hot flashes commonly show self-reported sleep disturbance, 27,28 which the current study corroborates with actigraphy data. The baseline actigraphy measures in this study showed no difficulty falling asleep, but moderate amounts of WASO (54-57 min), along with mildly reduced sleep efficiency (85% to 86%).…”
Section: Discussionsupporting
confidence: 88%
“…Studies of midlife women with hot flashes commonly show self-reported sleep disturbance, 27,28 which the current study corroborates with actigraphy data. The baseline actigraphy measures in this study showed no difficulty falling asleep, but moderate amounts of WASO (54-57 min), along with mildly reduced sleep efficiency (85% to 86%).…”
Section: Discussionsupporting
confidence: 88%
“…However, the lack of a control group can be considered as the limitation of our study. Suggesting our results, previous studies have shown that the frequency and severity of sleep apnea increases during menopause because of weight gain and decrease in estrogen and progesterone levels (12,13). Moreover, a previous report revealed that approximately 75% of the patients with OSA are suffering from obesity.…”
Section: Discussionsupporting
confidence: 85%
“…One prevailing theory with strong supportive evidence is that sleep serves a restorative function for the brain and body. Chronic insufficient sleep is a risk factor for a variety of psychological [9][10][11][12][13], neurological [14][15][16][17][18][19] and neurodegenerative pathologies [16], as well as cardiovascular and metabolic dysfunctions [20][21][22][23][24]. More recent findings from clinical studies reveal that women suffering from sleep disturbances and insufficient sleep are at greater risk compared with men for mood disorders such as depression [25], as well as metabolic [26] and cardiovascular dysfunction [23,[27][28][29].…”
Section: Overview Of Sleepmentioning
confidence: 99%